The Chicago–Carnegie Hubble Program: The JWST J-region Asymptotic Giant Branch Extragalactic Distance Scale - Abigail J. Lee; Wendy L. Freedman; Barry F. Madore; In Sung Jang; Kayla A. Owens; Taylor J. Hoyt (The Astrophysical Journal)
The J-region asymptotic giant branch (JAGB) method is a new standard candle based on the constant luminosities of carbon-rich AGB stars in the J band. The JAGB method is independent of the Cepheid and tip of the red giant branch (TRGB) distance indicators. Therefore, we can leverage it to both cross-check Cepheid and TRGB distances for systematic errors and use it to measure an independent local H _0 . The JAGB method also boasts a number of advantages in measuring distances relative to the TRGB and Cepheids, several of which are especially amplified when combined with JWST’s revolutionary resolving power. First, JAGB stars are 1 mag brighter in the near-IR (NIR) than the TRGB and can be discovered from single-epoch NIR photometry, unlike Cepheids, which require congruent optical imaging in at least 12 epochs. Thus, JAGB stars can be used to measure significantly farther distances than both the TRGB stars and Cepheids using the same amount of observing time. Dust extinction is also reduced in NIR observations and JAGB stars are ubiquitous in all galaxies with intermediate-age populations. We present a novel algorithm that identifies the optimal location in a galaxy for applying the JAGB method, so as to minimize the effects from crowding. We then deploy this algorithm in JWST NIRCam imaging of seven SN Ia host galaxies, to measure their JAGB distances, undertaking a completely blind analysis. In our Chicago–Carnegie Hubble Program H _0 results paper, by W. L. Freedman et al., we apply the JAGB distances measured in this paper to the Carnegie Supernova Program type Ia supernova sample, measuring a Hubble constant of H _0 = 67.80 ±2.17 (stat) ± 1.64 (sys) km s ^−1 Mpc ^−1 .